A CASE STUDY ON THE STUDENTS AND TEACHERS’ PERCEPTIONS ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION AND TEACHERS PROFESSIONAL COMPETENCIES AT SMP NEGERI 1 DENPASAR - Sudiatmika, I K.; Nitiasih, P.K.; Suarnajaya, I. W. (Universitas Pendidikan Ganesha, 2017)
This study aims at investigating the students and hard science teachers’ perceptions on the use of English as the language of instruction, the frequency of English used as the medium of instruction by hard science teachers, and the hard science teachers’ professional competences at SMP Negeri 1 Denpasar in science classes at RSBI (Rintisan Sekolah Bertaraf Internasional). The subjects of this study were the students and hard science teachers of SMP Negeri 1 Denpasar. The data on the frequency of English used by the teachers were gathered by recording the instructional process. The students and teachers’ perceptions and the teachers’ professional competencies were gathered using questionnaire and interview. The obtained data were then analyzed descriptively. The findings of the study showed that the students and hard science teachers of SMP Negeri 1 Denpasar have positive perceptions toward English. The frequency of the use of English as the medium of instruction varies. It showed that the mathematics teacher had a high frequency of English use. While the frequency of biology and a physics teacher in using English was considerably very low. The data also revealed that the hard science teachers had implemented professional competencies covering pedagogy, personal, social, and professional competencies.